ESSENSIAL OIL PADA Alpinia galanga (L.) WILLD. DAN PEMANFAATANNYA - Dr. Marina Silalahi, M.Si (Jurnal Pro-Life, 2017)
Alpinia galanga (L.) Willd., or lengkuas is native plant in Indonesia, which is used as medicine and spices. The use of plants as medicine and spices relates to its compounds of secondary metabolites esspecially the essential oil. This article aims to explain the uses and essential oil of Alpinia galanga. This article is based on literature offline and online media. Offline literature used the books, whereas online media used Web, Scopus, Pubmed, and scientific journals. Based on a study of ethnobotany galangal used as medicine, spices and insecticide. Alpinia galanga have 167 types of essential oils are 110 types in leaves , 108 types in stem, 107 types in rhizomes, and 108 types in root (Jirofetz et al. 2003). Essential oils of Alpinia galanga have biologycal activities as inhibit the growth of microbes that cause damage to the food and inhibit free radicals, so that to be potential as a natural food preservative and as an antioxidant. Keywords: Alpinia galanga, essential oil, antioksidan, dan antimikroba.